Thermotropic liquid-crystalline properties of extended viologen bis(triflimide) salts. Issue 6 (3rd May 2018) - Bhowmik, Pradip K.; Killarney, Shane T.; Li, Jessa Rose A.; Koh, Jung Jae; Han, Haesook; Sharpnack, Lewis; Agra-Kooijman, Deña M.; Fisch, Michael R.; Kumar, Satyendra
ABSTRACT: A series of extended, symmetric viologen triflimides were synthesised by the metathesis reaction of lithium triflimide with the respective viologen tosyalates in methanol. Their chemical structures were characterised by Fourier Transform Infrared, 1 H and 13 C Nuclear Magnetic Resonance spectroscopy and elemental analysis. Their thermotropic liquid-crystalline (LC) properties were examined by a number of experimental techniques including differential scanning calorimetry, thermogravimetric analysis, polarising optical microscopy and variable temperature X-ray diffraction. The viologen salts containing alkyl chain of two carbon and three carbon atoms were relatively low melting salts. Those of alkyl chains of four carbon and five carbon atoms formed ionic liquids at 88 and 42°C, respectively. Those of alkyl chain of 9, 10 and 11 carbon atoms were high melting salts, as high as 166°C. Those of higher alkyl chains of 16, 18 and 20 carbon atoms showed thermotropic LC phases forming SmC, SmA and an unidentified smectic (SmX) phases, and showed SmA to isotropic transitions at high temperatures. As expected, all the viologen triflimides had excellent stabilities in the temperature range of 338–365°C. Graphical Abstract: